2003
DOI: 10.1016/s0168-6496(02)00394-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial activity and community composition in stream water and biofilm from an urban river determined by fluorescent in situ hybridization and DGGE analysis

Abstract: Physiologic activity and community structure of planktonic and biofilm microbial communities in an urban river were analyzed using 5-cyano-2,3-ditolyl tetrazolium chloride (CTC) staining, fluorescent in situ hybridization (FISH) and denaturing gradient gel electrophoresis (DGGE) analysis of polymerase chain reaction (PCR)-amplified 16S rDNA fragments. Respiring bacteria estimated by CTC reduction were higher in biofilms (20%) than in stream water samples (12%). FISH analysis revealed that bacterial populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 28 publications
8
69
1
2
Order By: Relevance
“…The Proteobacteria were the predominant group in our investigation, accounting for 45 (50%) of 90 sequences, consistent with other investigations reporting high prevalence (20-50%) of Proteobacteria in bacterial communities in aquatic habitats [2,3,18] such as seawater [15,33], decaying salt marsh grass [7], and wastewater [7]. In potable water distribution systems, many bacterial species, including members of the Proteobacteria, Actinobacteria, low-G+C-content gram-positive bacteria, and Cytophaga-Flavobacterium-Bacterioides group, readily adhere to surfaces to form multispecies biofilms [39].…”
Section: Discussionsupporting
confidence: 92%
“…The Proteobacteria were the predominant group in our investigation, accounting for 45 (50%) of 90 sequences, consistent with other investigations reporting high prevalence (20-50%) of Proteobacteria in bacterial communities in aquatic habitats [2,3,18] such as seawater [15,33], decaying salt marsh grass [7], and wastewater [7]. In potable water distribution systems, many bacterial species, including members of the Proteobacteria, Actinobacteria, low-G+C-content gram-positive bacteria, and Cytophaga-Flavobacterium-Bacterioides group, readily adhere to surfaces to form multispecies biofilms [39].…”
Section: Discussionsupporting
confidence: 92%
“…Metacommunity theory posits that high dispersal rates and short generation times of microorganisms render geographical distances less important than the local environment for community assembly and ensuing biodiversity patterns 106 . For ecosystems with low residence times, such as streams, mass effects through high dispersal are assumed to maintain microbial populations even in less favourable habitats, thereby shifting community composition away from strict dependence on local environmental conditions 105 .…”
Section: Box 2 Metacommunity Ecologymentioning
confidence: 99%
“…The inoculation of soil bacteria in stream water is likely to be a major driver of this difference 57,58 . Streamwater bacteria have also been reported to be less active and their communities more temporally fluctuating than their biofilm counterparts 106 .…”
Section: Box 2 Metacommunity Ecologymentioning
confidence: 99%
“…However, the analysis of the chemical and physical characteristics of an ecosystem becomes limited when the objective is the understanding of its complexity as the biological components should also be taken into account. In this regard, many studies have demonstrated that knowledge of the structure and dynamics of the microbial community in rivers and streams is essential, mainly due to their role in several biogeochemical cycles (Brümmer et al, 2000;Araya et al, 2003;Kostanjšek et al, 2005). This is especially important for environments modified by anthropogenic action (Böckelmanna et al, 2000;Kenzaka et al, 2001;Tiquia, 2010).…”
Section: Introductionmentioning
confidence: 99%